Mineral Composition, Total Phenol Content and Antioxidant Activity of a Macrolichen Everniastrum cirrhatum (Fr.) Hale (Parmeliaceae). Issue 4 (2011) - Kekuda, T. R. Prashith; Vinayaka, K. S.; Swathi, D.; Suchitha, Y.; Venugopal, T. M.; Mallikarjun, N.
Abstract : In the present study, we investigated for the first time mineral composition, total phenol content and antioxidant activity of a foliose macrolichen Everniastrum cirrhatum (Fr.) Hale (Parmeliaceae) from Bhadra wildlife sanctuary, Karnataka, India. Mineral content of the lichen was estimated by Atomic absorption spectrophotometer after acid digestion. The secondary metabolites were detected by thin layer chromatography (TLC) and phytochemical assays. The lichen material was extracted with methanol in soxhlet apparatus. Total phenol content was estimated by folin ciocalteu method. Antioxidant activity was determined by DPPH, Ferric reducing and metal chelating assays. Among the principal elements, calcium was found in high concentration followed by magnesium, potassium and phosphorus. Among trace elements, iron was detected in high amount followed by zinc, manganese and copper. The DPPH radical scavenging activity was found to be dose dependent with an IC50 of 6.73 μg/mL. In ferric reducing assay, the absorbance increased with the concentration of extract suggesting reducing power. The extract exhibited good metal chelating activity with an IC50 value of 29.28 μg/mL. Total phenol content was 101.2 mg tannic acid equivalents per gram of extract. Phytochemical analysis revealed the presence of alkaloids, saponins, tannins and terpenoids. TLC revealed atranorin, salazinic acid and protolichesterinic acid. The lichen can be consumed as a source of minerals required for the body as appreciable amount of minerals has been detected. The marked antioxidant activity may be attributed to the presence of phenol content in the extract. Further studies on isolation of metabolites and their bioactivities are under investigation.